2017
DOI: 10.1002/mp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Small field dose measurements using plastic scintillation detector in heterogeneous media

Abstract: Small field dosimetry is particularly relevant to stereotactic radiation treatment. The accuracy of dose calculation for small static beams is critical to dose planning so would potentially affect the treatment outcomes in a heterogeneous medium. Our results have shown good agreement with plastic scintillation detector in both homogeneous and heterogeneous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A third example of discovery from the opposite direction of the original goal is the present study, which began as a quest to achieve submillimeter end-to-end accuracy on any stereotactic linac ( 75 ) but differences in outcomes among the various systems were observed. Soon, the tests validated that continuous live respiratory motion management indeed can achieve submillimeter end-to-end targeting accuracy and excellent dosimetric accuracy in a wide variety of situations ( 44 , 76 , 77 ), and the resulting clinical outcomes comparatively appear exceptionally good, as summarized in this study. This was also seen in the series of publications in the NTCP for SBRT issue of Seminars in Radiation Oncology ( 78 ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A third example of discovery from the opposite direction of the original goal is the present study, which began as a quest to achieve submillimeter end-to-end accuracy on any stereotactic linac ( 75 ) but differences in outcomes among the various systems were observed. Soon, the tests validated that continuous live respiratory motion management indeed can achieve submillimeter end-to-end targeting accuracy and excellent dosimetric accuracy in a wide variety of situations ( 44 , 76 , 77 ), and the resulting clinical outcomes comparatively appear exceptionally good, as summarized in this study. This was also seen in the series of publications in the NTCP for SBRT issue of Seminars in Radiation Oncology ( 78 ).…”
Section: Discussionsupporting
confidence: 60%
“…Systematic, standardized, and uniform data collection of treatment parameters and complications are lacking. Technically, physics measurements have shown that the even with respiratory motion management and in lung material, ray tracing algorithm can be off by up to 120%, although improved measurements by some of the same authors later matched the Monte Carlo algorithm within 3% ( 77 , 79 ). Similarly, when motion management techniques were used without multiple fiducials and synchrony tracking, the risk of duodenal complications was found to be five times higher ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these scintillators can perform real-time measurements with a high spatial resolution. This makes plastic scintillation detectors (PSD) attractive for small fields or highly modulated beam measurements (Xue et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these scintillators can perform real-time measurements with a high spatial resolution. This makes plastic scintillation detectors (PSD) attractive for small fields or highly modulated beam measurements [4].…”
Section: Introductionmentioning
confidence: 99%